Employee operating Beckman (Berkeley) Time Interval Meter at Hercules Port Ewen plant - Hercules Incorporated (1962)
General view of an unidentified employee operating a Beckman (Berkeley Division) Time Interval Meter at the Hercules Powder Company plant in Port Ewen, New York. Time Interval Meters were commonly used for a range of industrial applications, including ballistics research and to measure the timing of relays and shutters, as well as viscosity, velocity, and elasticity. Formed in 1912 as part of an anti-trust settlement with DuPont, the Hercules Powder Company (later Hercules Inc.) specialized in the manufacture of explosives and smokeless powders. The company's Port Ewen plant produced a range of special detonators designed for military use, as well as construction jobs that required blasts of dynamite, such as the clearing of quarries, mines, and tunnels.
Keywords: Detonators; Employees; Chemical industry; Scientific apparatus and instruments; Propellants; Hercules Incorporated; Explosives--Testing; Corporations; Explosives; Machinery; Beckman Instruments, Inc.